Formulation and Evaluation of the Sun Protection Factor (SPF) of a Chemical Sunscreen Containing Molecularly Distilled Heavy Fraction Patchouli Oil - Nadia Isnaini; Fajar Fakri; Vicky Prajaputra; Hanifa Rifdah Aiman; Novi Kurnia Rizki (Postgraduate, University of Mataram, 2025)
The Sun Protection Factor (SPF) indicates the level of protection that a sunscreen formulation provides against ultraviolet (UV) radiation. The heavy fraction patchouli oil obtained via molecular distillation contains 90.48% patchouli alcohol, which exhibits antioxidant activity. This study aimed to determine the SPF value of the heavy fraction patchouli oil and to evaluate the characteristics and SPF values of emulgel-based chemical sunscreens. Patchouli oil demonstrated an in vitro SPF of 37.63, classified as ultra-protection. Sunscreen formulations were prepared using the beaker method, with patchouli oil incorporated at varying concentrations, including 0% (control), 0.25% (F1), 0.5% (F2), and 1% (F3). The formulations were evaluated for physicochemical characteristics, stability, and skin safety. They exhibited an opaque white to ivory color, with a pH range of 5.2 to 6.4, viscosity between 2011 and 2924 cPs, spread ability of 4 to 6 cm, adhesion time of 5.38 to 8.28 seconds, and an oil-in-water (O/W) emulsion type. The SPF values of the sunscreen formulations ranged from 8.85 to 29.02, with F3 achieving an SPF of 29.02 and classified as ultra-protection. All formulations met the established quality standards, remained stable during storage, and caused no irritation in human volunteers. These findings indicate that the heavy fraction of patchouli oil has great potential as an active ingredient for chemical sunscreen products.